Exploring the Connections Between Environmental Changes and Health Issues Like Respiratory Diseases and Infectious Outbreaks: A Critical Analysis (The Review of Diabetic Studies, 2024)
Environmental changes, such as climate change, air pollution, and deforestation, have profound impacts on public health, contributing to the rising prevalence of respiratory diseases and the increased frequency of infectious outbreaks. This paper critically analyzes the linkages between environmental shifts and health outcomes, focusing on how these changes exacerbate respiratory conditions like asthma and COPD, while facilitating the spread of vector- and waterborne diseases. The analysis highlights the disproportionate impact on vulnerable populations and explores strategies for mitigating these health risks through climate adaptation, public health infrastructure improvements, and global policy interventions. The paper calls for a more integrated approach to addressing the intersection of environmental change and public health crises.